Resenhas - Cappelin, Paola; Leite, Miriam Moreira; Garcia, Marco Aurélio; Prado, Danda; Lamego, Valéria; Cunha, Maria Carneiro da; Lavinas, Lena; Nunes, Clarice; Marco, Valéria de; Callado, Ana Arruda (Revista Estudos Feministas, 1992)
resenhas